The Profile of Lung Adenocarcinoma Patients with Positive EGFR Mutation - Pandu Wiriansya, Edward; Ainun; Ratu, Puspa; Muhammad Reza Cesarian Noor, Andi (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Background: The high mortality rate in pulmonary carcinoma is a problem encountered in various countries, including Indonesia. According to WHO, there are 2.09 million people affected by lung cancer and 1.76 million deaths due to lung cancer worldwide. This study was aimed to determine the profile of lung adenocarcinoma patients with positive EGFR mutation. Methods: The study was descriptive study with cross-sectional approach using secondary data obtained from medical records of lung adenocarcinoma patients. Results: The present study revealed that lung adenocarcinoma was found higher in patients with age >40 years old (93.9%) compared to those with age <40 years old. It was also higher in male (66.7%) than in female patients. Most patient with lung adenocarcinoma were at the IIIB stage (42.4%). It was also reported that higher cases was found in patients with history of smoking more than 15 years (42.4%). Hemoptoe was the most reported clinical symptoms in patients with lung adenocarcinoma (87.9%). Lung adenocarcinoma was also observed higher in patients without family history of pulmonary adenocarcinoma (81.8%). Seventeen of 33 EGFR mutations (51.5%) were observed in exon 19 and fourteen (48.5%) were in exon 21. Conclusion: The most common EGFR mutation lung adenocarcinoma was observed in exon 19.